Comparison of hemodynamic changes and level of spinal anesthesia in patients with hypothyroidism and control group undergoing caesarean section with spinal anesthesia: a case-control study - Fatemeh Eftekharian; Ahmad Rastegarian; Afroz Kargarfard; Navid Kalani; Farideh Mogharab; Shekefeh Mousavi; Mohammad Rahmanian; Naser Hatami; Reza Sahraei (Mashhad University of Medical Sciences, 2023)
Introduction: Pregnancy has a significant effect on the thyroid gland and its function. Hypothyroidism in pregnancy is defined as an increase in serum TSH levels. The present study was conducted with aim to investigate the amount of hemodynamic changes and the level of spinal anesthesia in hypothyroid patients undergoing caesarean section with spinal anesthesia and comparing it with the control group.Methods: In this case-control study, 83 patients aged 18-42 years who referred to Motahari Hospital in Jahrom city for caesarean section were studied in two hypothyroid (n=42) and control (n=41) groups. The level of spinal anesthesia, systolic, diastolic and mean arterial blood pressure and heart rate were measured and recorded before the administration of anesthetic, 1, 15, 30, 45 and 60 minutes after anesthesia and at the time of entry and exit from recovery. Data analysis was done by SPSS software (version 21) and repeated measurement, Cochran, analysis of variance and chi square tests. P<0.05 was considered statistically significant.Results: There was a significant difference in the frequency of spinal anesthesia between hypothyroid patients undergoing caesarean section with spinal anesthesia and the control group (p<0.001). There was no significant difference between the groups of patients with hypothyroidism and the control group in terms of mean systolic and diastolic blood pressure before and 1 minute after anesthesia, 15, 30, 45 and 60 minutes after anesthesia and at the time of entry and exit from recovery (P<0.05).Conclusion: Although the use of spinal anesthesia in pregnant mothers with hypothyroidism reported a higher level of anesthesia during the operation compared to the control group, the difference in mean arterial pressure and heart rate was not clinically significant between the groups. Based on the present study, it seems that there is no need to change the spinal anesthesia protocol for patients with hypothyroidism.